ANALISA KEBIJAKAN PENGATURAN JARAK IDEAL KELAHIRAN ANAK DALAM UNDANG-UNDANG NOMOR 52 TAHUN 2009 TENTANG PERKEMBANGAN KEPENDUDUKAN DAN PEMBANGUNAN KELUARGA - Khairunnisa Hasibuan; Gusliana HB; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Law Number 52 of 2009 concerning population development and familydevelopment, population is matters relating to the number, structure, growth,distribution, mobility, distribution, quality, and welfare conditions relating topolitics, economics, socio-culture, religion and the environment resident. Inwriting, the author focuses on the ideal spacing of child births in Law Number 52of 2009 concerning Population Development and Family Development. Thepurpose of writing this thesis is first to find out how to regulate the ideal spacingof child births in Law Number 52 of 2009 concerning Population Developmentand Family Development. Second, to find out how the ideal concept of spacingchildren's births in Indonesia is in Law Number 52 of 2009 concerningPopulation Development and Family Development.The author conducted research using normative juridical methods orliterature studies in order to obtain secondary data through documentary studies,namely by studying and analyzing descriptively comparative laws and regulationswith theories that have a relationship to the problems studied.From the results of the study there are two main things that can beconcluded, firstly, the regulation regarding the ideal spacing of child births in lawnumber 52 of 2009 concerning population development and family development isregulated in article 4 and article 21, the second is the ideal concept in regulationspacing of child births in Indonesia in law number 52 of 2009 concerningpopulation development and family development is 18-23 months between twopregnancies is the best and most ideal because the mother has time to recover andreplenish the body's resources.The author's suggestion, in this study, is to suggest that the implementationof the central government and local governments issue further regulations interms of setting the ideal spacing for child births so that there is legal certainty,setting the ideal spacing for child births will have an impact on mothers andbabies so that the health of mothers and babies is maintained and also applies tothe economic, social and cultural sectors of society.Keywords: Policy, Ideal Distance of Child Birth, Law Number 52 of 200.